Stylosanthes Gracilis in Conservation Farming - Pandey, S.N.; Teotia, S.P. Singh (Journal of Soil and Water Conservation, 2022)
Success in various conservation farming prac-tices requires the use of different kinds of plants. As the land has different land capability classes the plants also have varying capabilities for proper growth. The stylosanthes gracilis (Brazi-lian Lucerne) has a special place for the upper Damodar Catchment because it can produce good cover on the eroded and shallow soils of this region. The seeds of Stylosanthes gracilis were collected from Ranchi Agriculture College, Kanke, Ranchi during the year 1958, and its performance was observed at Deochanda Experiment Station of Soil Conservation Department DVC under rainfed conditions. The seeds were first sown in earthen pots and when the seedlings were four weeks old, two to three seedlings wore transplanted at a spacing of 2 ft X2 ft in plots of size 15 ft. X 10 ft. The seedlings were seen to establish after three to five days. The observations were recorded with respect to growth habit, time of flowering, aggressiveness, resistance to drought, number of cuttings with green forage yield and suitability for erosion control.